Frailty and outcomes following revascularization of lower-extremity peripheral artery disease: Insights from the Vascular Quality Initiative (VQI). (June 2022) - Al-Damluji, Mohammed S; Smolderen, Kim G; Meng, Can; Dai, Feng; Nanna, Michael G; Sumpio, Bauer; Henke, Peter; Mena-Hurtado, Carlos
Background: Multiple frailty screening tools are implemented; however, it is unclear whether they perform in a comparable way for both frailty detection and prediction of perioperative outcomes in patients undergoing lower-extremity revascularization. Methods: Patients undergoing lower-extremity revascularization were identified from the Vascular Quality Initiative (VQI) national database. Two cohorts were established based on the revascularization type (percutaneous vascular interventions (PVI) or lower-extremity bypass). Frailty was assessed by the 5-item modified frailty index (mFI-5) and the VQI-derived risk analysis index (RAI). Results: Out of 134, 081 patients undergoing PVI, frailty was identified in 67% by mFI-5 and 28% by RAI. Similarly, out of 41, 316 patients in the bypass cohort, frailty was identified in 69% by mFI-5 and 16% by RAI. There was little agreement between the two frailty tools for both vascular cohorts (PVI: kappa: 0.17; bypass: kappa: 0.13). In an adjusted analysis, frailty as assessed by mFI-5 and RAI was associated with higher odds of mortality in both cohorts ( p < 0.001). A significant association between frailty and unplanned amputations was only noted in the bypass cohort when RAI was applied (OR: 1.50, p < 0.01). The addition of frailty to traditional PAD risk factors marginally improved model performance to predict mortality and unplanned major amputations. Conclusion: There was significant variation in frailty detection by mFI-5 and RAI. Although frailty was associated with mortality, the predictive value of these tools in predicting outcomes in PAD was limited. Future research should focus on designing new frailty screening tools specific to the PAD population.